(3JYdjb GdaQGFO Ydi JSgjd GdahGFOs - (3eMeO Hf CHj HcQ Hf YeQ Hf CHj HcQ Hf eMeO, GdeNRhej GdbQTj, HOQ GdOjf GdeYQha HGHf GdOeGejfj , J (B827 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
"(3HGH GdUaI GdeTHgI HGSe GdaGYd(B" (3Cj HGH jPcQ CYeGd GdUaGJ hbO cGf jfHZj Cj jJcde Ydi UjZJg ChdkG s
(3BNQgG (B:s
(3hjcJH jGA Ydi efGSHI MQcJgG, CVaJ, fMh ef NWjFI Ch de JUa fMh ef GdcdG hgfG Je GdcdGe aj JYdjb GdaQGFO Ydi JSgjd GdahGFO s
(3fSNI KGdKI JJab BNQgG eY BNQ GdfSNI GdKGfjI HGNJdGa aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs